Cognitive Behavioral Therapy untuk meningkatkan Positive Body Image Remaja Putri: Sebuah Literatur Review - Ardiani Febriana; Eka Wahyuni (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
Adolescence is a transition from childhood to adulthood characterized by significant physical, emotional and social changes. Physical and emotional changes that occur in adolescence form a new self-image for adolescents, especially in terms of body image. Body Image is a sensitive and complex issue that affects many individuals, especially women. Cognitive Behavioral Therapy approach is one of the approaches used to intervene body image problems. This literature review aims to map various studies on the intervention of the Cognitive Behavioral Therapy approach in the body image problems of adolescent girls. This research uses a literature review method or literature study. Literature review technique or literature study with sources from google scholar database, sagepub, researchgate, PubMed and Wiley. The results obtained 25,254 journals related to three keywords namely